2016
DOI: 10.1093/jac/dkw264
|View full text |Cite
|
Sign up to set email alerts
|

A feasibility service evaluation of screening and treatment of group A streptococcal pharyngitis in community pharmacies

Abstract: ObjectivesThe UK 5 year antimicrobial resistance strategy recognizes the role of point-of-care diagnostics to identify where antimicrobials are required, as well as to assess the appropriateness of the diagnosis and treatment. A sore throat test-and-treat service was introduced in 35 community pharmacies across two localities in England during 2014–15.MethodsTrained pharmacy staff assessed patients presenting with a sore throat using the Centor scoring system and patients meeting three or all four of the crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
64
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(68 citation statements)
references
References 15 publications
2
64
2
Order By: Relevance
“…These roles will vary based on the pharmacist resources available in various outpatient settings such as community pharmacies, ambulatory care clinics, urgent care centers, and emergency departments. In the community pharmacy setting, pharmacists can assist patients in infection prevention through pharmacist‐administered vaccines, supportive care or symptomatic relief recommendations for common respiratory viral infections, patient education, antibiotic prescription reconciliation, allergy assessment interviews, and potentially for point‐of‐care testing to guide clinical decision making in appropriate antibiotic prescribing . Ambulatory care, urgent care, and emergency department settings may utilize pharmacist resources for additional initiatives as well including, but not limited to health care professional and patient education, allergy assessment interviews, collaborative practices for AS endeavors, and development of evidence‐based treatment algorithms for common outpatient infections in the electronic medical record to minimize antibiotic prescribing variation …”
Section: Discussionmentioning
confidence: 99%
“…These roles will vary based on the pharmacist resources available in various outpatient settings such as community pharmacies, ambulatory care clinics, urgent care centers, and emergency departments. In the community pharmacy setting, pharmacists can assist patients in infection prevention through pharmacist‐administered vaccines, supportive care or symptomatic relief recommendations for common respiratory viral infections, patient education, antibiotic prescription reconciliation, allergy assessment interviews, and potentially for point‐of‐care testing to guide clinical decision making in appropriate antibiotic prescribing . Ambulatory care, urgent care, and emergency department settings may utilize pharmacist resources for additional initiatives as well including, but not limited to health care professional and patient education, allergy assessment interviews, collaborative practices for AS endeavors, and development of evidence‐based treatment algorithms for common outpatient infections in the electronic medical record to minimize antibiotic prescribing variation …”
Section: Discussionmentioning
confidence: 99%
“…Analysing the outcomes of pharmacist prescribing in the United Kingdom has led to the realisation of the benefits that this practice brings along. Thornley et al . have shown that a community pharmacy‐based screening and treatment service, run by trained pharmacy staff, using point‐of‐care testing has the potential to reduce antibiotic pressure from patients and help in the effort to reduce the emergence of antibiotic resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Analysing the outcomes of pharmacist prescribing in the United Kingdom has led to the realisation of the benefits that this practice brings along. Thornley et al [27] have shown that a community pharmacy-based screening and treatment service, run by trained pharmacy staff, using point-of-care testing has the potential to reduce antibiotic pressure from patients and help in the effort to reduce the emergence of antibiotic resistance. Having pharmacists as non-medical prescribers allows general practitioners to concentrate more on diagnosis and procedures, helps reduce drug expenditure and wastage, helps improve adherence to guidelines whilst reducing the risks of prescribing and communication errors, helps improve patient care through easier medication access and reduce waiting times for patient review.…”
Section: Implications For Practicementioning
confidence: 99%
“…As one of eight interventions chosen for the second year of the programme, the sore throat project is based on a non-NHS service piloted in 35 community pharmacies owned by Boots. People (aged 12 years or older) were assessed using Centor criteria and those identified as being at increased risk of a bacterial infection were offered a throat swab and rapid antigen test with the option of an antibiotic if the test was positive 3. Patients were charged for the cost of the service and the supply of antibiotic.…”
mentioning
confidence: 99%